If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(f + 3) = 7(f + 5) Reorder the terms: 9(3 + f) = 7(f + 5) (3 * 9 + f * 9) = 7(f + 5) (27 + 9f) = 7(f + 5) Reorder the terms: 27 + 9f = 7(5 + f) 27 + 9f = (5 * 7 + f * 7) 27 + 9f = (35 + 7f) Solving 27 + 9f = 35 + 7f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-7f' to each side of the equation. 27 + 9f + -7f = 35 + 7f + -7f Combine like terms: 9f + -7f = 2f 27 + 2f = 35 + 7f + -7f Combine like terms: 7f + -7f = 0 27 + 2f = 35 + 0 27 + 2f = 35 Add '-27' to each side of the equation. 27 + -27 + 2f = 35 + -27 Combine like terms: 27 + -27 = 0 0 + 2f = 35 + -27 2f = 35 + -27 Combine like terms: 35 + -27 = 8 2f = 8 Divide each side by '2'. f = 4 Simplifying f = 4
| 2(y+6)-3=19 | | sqrt(528)= | | 24x+6x-8x+5x-36x=3-24-24+18 | | x-0.25x=1 | | 6(x-2)=3(x+8) | | Y1/2x-2 | | 0.1(n+76)=0.5n | | 6(3x+1)-14(2-4x)=3(-5x-4)+49x | | 1+(2+y)=10 | | x^2-7p-120=0 | | N+76=n | | (2x-1)2=7 | | 6.9x-2.6=18.1 | | 6x(2-x)=52 | | 25+4x=6x+9 | | 3(4x-1)-5(x+7)=3(x+1) | | x-1/5=x/2 | | 9/x=2/7 | | 4x+6*2-6=12x | | 9x-5=12y | | 5(6z-1)-5(z+1)=23(z+1) | | 4^3x-1=1/64 | | y^2+18y+45= | | 3000000=1.55x^2-5.1x+197 | | 4+8(x-6)=6-9(x-8) | | 5x-y^2-3=0 | | 3x+11y=33 | | (-7-3m^3-7m)-(-7m^3-3)=0 | | 3d*2+14d-5= | | 0.5(6x-20)+32=64 | | 5x^2+36x+2=0 | | 8x-44=-9x+78 |